Burkholderia Cepacia Complex: A Cause of Dental Caries in Uyo, Southern Nigeria State - Udoh, Mary Athanasius; Onwuezobe, Ifeanyi Abraham; Umo, Anthony Nathaniel; Kingsley, Victoria Intimate; Shehu, Amina Jummai (African Journal of Clinical Medicine and Pharmacy Research, 2025)
Background. Dental caries is a common oral disease worldwide, and it affects above 90% of the population. Several bacteria species are implicated in caries; many of which are the normal microbiota of the buccal cavity. These bacteria are often opportunistic. Caries process starts from proliferation of oral flora, establishment of non-oral bacteria, and production of biofilm leading to plaque formation. This serves as a shield for pathogenic bacteria from being eliminated by antibiotics. The aim of this study was to find out the dominant bacteria of caries in Uyo, and factors that influence their occurrence. Methods. One hundred and twenty plaque samples of participants were analyzed using standard laboratory methods; biochemical and antibiotics susceptibility tests results were obtained using Vitek 2 System (bioMe´rieux). CTX-M, TEM and OXA resistance genes were analyzed for, and were amplified on an ABI 9700 Applied Biosystems thermal cycler using pre-determined conditions set. Results. Nine (9 (33.3%) Gram-positive bacteria and 18 (66.7%) Gram-negative bacterial isolates were obtained. The dominant isolate was Burkholderia cepacia complex 7 (25.9%), while some of the least were; Pediococcus pentosaceus 1 (3.7%) and Klebsiella pneumoniae 1 (3.7%). Ceftazidime was the antibiotic B. cepacia were mostly resistant to, but greatly sensitive to Amikacin and Tobramycin. Six B. cepacia isolates (out of 7 identified) were further analyzed molecularly by 16s rRNA sequencing. Burkholderia cenocepacia (2 isolates) and Burkholderia cepacia (4 isolates) were the two species identified. Conclusions. B. cepacia complex is known to cause major complications in cystic fibrosis and immunocompromised patients. Therefore, it is a major health challenge for it to be implicated in caries in Uyo, as it can easily spread to different parts of the body (the lungs inclusive) through the carious tooth. It is also an established fact that B. cepacia resistance genes rapidly disseminate, making treatment difficult.